Neuromarketing y la fidelización de clientes en el centro veterinario campovet ubicada en el barrio Santan de la ciudad de Latacunga en el período 2014 – 2015 - Lema Yugla, Norma Ximena (2015)
This research aims; It retain customers through marketing strategies oriented neuromarketing Veterinary Center "CampoVet" located in the Santan area of the city of Latacunga, for which a F.O.D.A. analysis was performed in order to investigate the current situation that is developing the internal and external activities, to detect, correct and leverage the strengths, weaknesses, opportunities and threats, thus detecting the main problem is the low loyalty by customers and ignorance of the business image, the methodology used was deductive, analytical, synthetic and statistical method, documented and field, using the techniques and tools of research and the survey, the questionnaire bibliographic research and observation forms , so that through this project aims to help the business to greater competitive advantage and managed to ensure that the business requires neuromarketing strategies to retain customers….